Isotherm and kinetic models of SO2 adsorption on palm kernel shell-activated carbon and xerogel blends: Effect of flow rate and contact time - Ali Mohamed Saleh; Azil Bahari Alias; Syed Shatir A. Syed Hasan; Ali H. Jawad; Thaer Abdulwahhab Shihab; Obed M. Ali; Wan Azlina Wan Ab Karim Ghani; Hadi Hamdi Mahdi; Noah Mohammed Saleh; Omer Khalil Ahmed (Results in Engineering)
Sulphur dioxide (SO2) is released into the atmosphere when coal-fired power plants run, which may substantially impair the environment. SO2 in flue gas causes respiratory difficulties and acid rain, and as energy consumption rises, the amount of SO2 emitted into the environment also rises. SO₂ can effectively be removed from gases or air streams through adsorption, where it is captured and retained onto a solid surface, such as activated carbon. This research focuses on developing and evaluating a composite adsorbent made from palm kernel shell-activated carbon and xerogel (PKSACX) for the adsorption of sulphur dioxide (SO₂). The main objectives are to study the modelling of adsorption isotherm (Thomas, Yoon-Nelson, and Adam-Bohart models) and to determine the adsorption kinetics (pseudo-first and pseudo-second order) of the performance of SO2 adsorption on a blended series of palm kernel shell-activated carbon and xerogel. Based on the result obtained, the adsorption process mathematically described by the Thomas and Yoon-Nelson Model is the best model for SO2 removal compared to the Adam-Bohart model. Pseudo-First Order and Pseudo-Second Order kinetic models were utilized. The correlation coefficient (R2) was used to assess the equation's suitability. The PKSACXB adsorption processes suit both the pseudo-first and pseudo-second order equations. This indicates that throughout the adsorption process, both physisorption and chemisorption occur.